Pengaruh Pemberian Ekstrak Akar Pasak Bumi Terstandar terhadap Gambaran Histopatologik Testis dan Konsentrasi Testosteron pada Tikus - FARIDA HAYATI; SITARINA WIDYARINI; LUKMAN HAKIM; NGATIDJAN NGATIDJAN; MUSTOFA MUSTOFA (Fakultas Farmasi Universitas Pancasila, 2012)
The root of pasak bumi (Eurycoma longifolia, Jack) is one of plant from Indonesia known as aphrodisiac. This study was conducted to evaluate the influence of pasak bumi standardized extract to testosterone level and histopathological changes of the testes in male Wistar rats. Sample were 50 adult male rats aged 3 4 months were divided into 5 groups. Group I (control) was given distilled water, group II (positive control), was given testosterone (Andriol ®), group III, IV, and V were each given a standardized extract of the roots of pasak bumi doses of 50, 100, and 200 mg/kg of body weight, respectively. The extract was given orally twice a day for six days and forty nine days and then testes was taken out on 7th and 50th day. Testosterone level was assayed on 7th and 50th day by the ELISA methods. The results were analyzed using one way ANOVA, and post hoc Dunnet (2-sided) (p < 0.05). The data of this study shows that treatment with water extract of pasak bumi root influence the number of Leydig cells that would also increase the concentration of testosterone in Wistar male rats positively at a dose of 100 mg/kg and 200 mg/kg body weight.